New Applications of the (G?/G, 1/G)-Expansion Method - Inan, I. E.; Ugurlu, Y.; İnç, Mustafa (Polish Acad Sciences Inst Physics, 2015)
In this paper, we study general solutions of the new fifth order nonlinear evolution and the Burgers KP equations with the aid of the two variables (G'/G, 1/G)-expansion method. The kink, bell-shaped solitary wave, periodic and singular periodic solutions are obtained. Finally, the numerical simulations add to these obtained solutions.
Keywords: Nonlinear Evolution-Equations; Differential-Difference Equation; Traveling-Wave Solutions; Symbolic Computation; Mathematical Physics; Explicit Solutions; Kink Solutions; Transformation; Models